A TRISTE E DESCONHECIDA HISTÓRIA DO TRIBUNAL DE SEGURANÇA NACIONAL - Vladimir Passos Freitas (LexCult, 2020)
Few people are aware that Brazil had a National Security Court, created under the dictatorial regime of Getúlio Vargas, and that, despite its short duration, decided cases of great political relevance. Created by Law 244, of September 11, 1936 and extinguished in 1946, located in the Federal District, at that time in Rio de Janeiro, with jurisdiction throughout the national territory, this Court used to judge, in the first instance, crimes considered to be against political and social institutions, through its own criminal process, characterized by the most serious offenses to the right of defense. The way it was created and maintained made the National Security Court the most serious affront to the principles of the broad defense and natural judge. This research seeks to reveal it to students and legal professionals, as an example of what should not be done.